A study on the use of role-plays in developing the english speaking skills of 10th graders from Kim Lien high school = Nghiên cứu về việc sử dụng hoạt động đóng vai trong việc phát triển kĩ năng nói tiếng Anh cho học sinh lớp 10 trường thpt Kim Liên - Hoàng, Hải Chi (2020)
Of four skills taught in tertiary education, speaking has become the focus of not only the educators but also the learners because of its good response to society’s demand. Under the effect of communicative language teaching (CLT), out-dated teaching methods have therefore been shifted to communicate approach with the exploitation of a variety of speaking activities including role-play. As an attempt to explore the effectiveness of role-plays in speaking classroom for a certain group of learners, namely, the 10th Kim Lien high school graders, this paper will shed light on four dimensions. It describes the perception of both students and teachers on the use of role-plays, the ways of organizing a role-play, the challenges during the activity and its results towards the improvement of the students’ speaking skills. For the achievement of those targets, 200 students and 3teachers are involved in completing the questionnaires and interviews. Observing classes is also adopted so that the researcher can examine more closely the results. The research consists of two main phrases at which the first one is for observing and interviewing from the beginning of the survey while the second is for collecting questionnaires’ results. In the paper, it is displayed that a vast majority of students and teachers have a good attitude towards using role-plays. By applying this technique, the students have chance to work in teams as well as motivate themselves to speak English. Based on the concrete analysis of the survey, many aspects of speaking skills are confirmed to be attained by the learners when they participate in the activity. Moreover, the participants concede that they find their speaking ability much better, which implies how successful role-plays are in learning and teaching a language.